Advantages and disadvantages of the correction of the aortic heart disease and aortic aneurysm through the upper midrange J-shaped mini- sternotomy - Kravchenko, V. I.; Kravchenko, I. M.; Tretyak, O. A.; Tarasenko, Yu. M.; Larionova, O. B.; Lytvynenko, V. A. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Notwithstanding the advantages of longitudinal sternotomy as a surgical approach to aneurysms corrections, new profound researches found some shortcomings of that approach. Along with heart surgery technology improvement, cardio surgeons around the globe continue working out new methods of surgery that will offer an alternative and ensure the carrying out of less traumatic operations.